Kiitigaan Medgwe Nishnawbe - Good Things Growing: Literature Reviews to Inform Indigenous Food Self-Determination Planning and Evaluation - Choubak, Melisa; Giddings, Carla; Ferguson, Mary; Ferguson, Emmett; Murray, Janet (2018)
This project summary offers a short description of a project undertaken by the Community Engaged Scholarship Institute in collaboration with local consulting firms. Researchers produced an annotated bibliography and a literature review for the Nishnawbe Aski Nation in order to inform community-based food system planning and evaluation processes within four remote Ontario First Nations communities.